(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. This study was aimed to assess the ratio of total cholesterol (TC) to high-density density lipoprotein cholesterol (HDLC) and plasma nitrate levels in patients with ischemic nephropathy receiving statins and niacin extended release (NER). Materials and Methods. Kidney disease patients with a history of at least 5 year of diabetes mellitus or 10 year of hypertension were screened by renal artery Doppler ultrasonography. Participants were randomly assigned into two groups to receive atorvastatin, 20 mg/d, with and without NER, 500 mg/d, for 16 weeks. Serum levels of lipid profile, creatinine, and nitrate were compared before and after the study. Results. Fifty-four patients received the statin and 51 received statin-NER combination. Both statin and statin-NER groups demonstrated significant decreases in plasma levels of TC and low-density lipoprotein cholesterol. Triglyceride and very low-density lipoprotein cholesterol were significantly lowered only with statin-NER combination. The increase in HDLC level was found in both groups, but significant only with statin-NER combination therapy (P < .001). Atorvastatin combined with NER reduced TC/HDLC ratio almost double as compared with that of atorvastatin alone (102% and 36.6% reduction, respectively). A similar pattern was observed for nitrate levels (33% and 65%, respectively). Conclusions. These findings indicated that a reduction in TC/HDLC ratio improves endothelial function in renovascular disease and use of NER in combination with atorvastatin may provide better outcomes. This could be helpful in attenuating further vascular damage and associated systemic complications.